Cerebrolysin as an adjuvant therapy after mechanical thrombectomy in large vessel occlusion cardioembolic stroke: a propensity score matching analysis - ElBassiouny, Ahmed; Shehata, Mohamed S. A.; Zaki, Amr S.; Bedros, Rady Y.; El-Sudany, Ayman Hassan; Nasser, Azza Abdel (Frontiers in Neurology, 2025)
IntroductionEndovascular recanalization therapy has demonstrated considerable efficacy in the treatment of acute ischemic stroke (AIS). However, not all patients appear to benefit on the long term from this therapy. No studies have assessed the role of Cerebrolysin following mechanical thrombectomy (MT). The present study was conducted to evaluate the safety and efficacy of Cerebrolysin as add-on treatment to MT in patients with cardioembolic AIS.MethodsThis study evaluated 150 patients admitted to the stroke unit. Data were prospectively collected from 75 patients with cardioembolic AIS and National Institutes of Health Stroke Scale (NIHSS) ≥10, who underwent successful MT ± recombinant tissue plasminogen activator (rt-PA). Patients fulfilling inclusion criteria were consecutively enrolled and treated with Cerebrolysin at a daily dose of 30 ml for 14 days, with treatment initiated within 8 h following MT. Patients were compared with a historical control group of 75 well-matched patients who underwent MT ± rt-PA but did not receive Cerebrolysin. The primary outcome measure was a favorable modified Rankin Scale (mRS = 0–2) at day 90. Secondary parameters included the NIHSS, the Montreal Cognitive Assessment (MoCA), the rate of hemorrhagic transformation, mortality, and adverse events. Propensity score matching was performed to match the variables between the compared groups.Results and discussionThe overall results demonstrated that patients treated with Cerebrolysin exhibited a significantly higher proportion of mRS scores of 0–2 at day 90 (64% vs. 34.7%) in comparison to the control group. This finding was consistent with lower NIHSS and mRS scores at all study visits, and a lower any hemorrhagic transformation rate (20% vs. 57.3%). Furthermore, the logistic regression analysis revealed that patients with favorable mRS scores were less likely to undergo hemorrhagic transformation (odds ratio = 2.75, 95% confidence interval = 1.17, 6.45; p = 0.002). The administration of Cerebrolysin as an add-on treatment resulted in a significant benefit for AIS patients following MT, characterized by an improvement in mRS and NIHSS scores, along with a reduced rate of hemorrhagic transformation. The administration of Cerebrolysin was safe and well tolerated. Further studies are required to confirm these results.